2022
DOI: 10.3389/fendo.2022.1042878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of type 2 diabetes mellitus in rotator cuff tendinopathy: Development and analysis of a novel rat model

Abstract: ObjectiveTo establish and validate an intact rotator cuff rat model for exploring the pathophysiological effects of type 2 diabetes on the rotator cuff tendon in vivo.MethodsA total of 45 adult male rats were randomly divided into a control group (n = 9) and type 2 diabetes group (n=36). The rats were sacrificed at 2 weeks (T2DM-2w group, n=9), 4 weeks (T2DM-4w group, n=9), 8 weeks (T2DM-8w group, n=9), and 12 weeks (T2DM-12w group, n=9) after successful modeling of type 2 diabetes. Bilateral shoulder samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Some studies have shown that diabetes alters the physical and chemical properties of tendons and the arrangement of collagen fibers, extracellular matrix composition, and biomechanics in a high-glucose microenvironment ( 5 ). The current study demonstrated that the degree of tendinopathy gradually worsens and the biomechanical properties decrease in the supraspinatus tendon of rats at 2, 4, 8, and 12 weeks after diabetes induction ( 6 ). However, studies on how diabetes leads to the continuous progression and deterioration of rotator cuff tendinopathy have not been reported; also, the changes in endogenous small molecules and the involved biological pathways with the progression of diabetes remain unclear.…”
Section: Introductionmentioning
confidence: 64%
“…Some studies have shown that diabetes alters the physical and chemical properties of tendons and the arrangement of collagen fibers, extracellular matrix composition, and biomechanics in a high-glucose microenvironment ( 5 ). The current study demonstrated that the degree of tendinopathy gradually worsens and the biomechanical properties decrease in the supraspinatus tendon of rats at 2, 4, 8, and 12 weeks after diabetes induction ( 6 ). However, studies on how diabetes leads to the continuous progression and deterioration of rotator cuff tendinopathy have not been reported; also, the changes in endogenous small molecules and the involved biological pathways with the progression of diabetes remain unclear.…”
Section: Introductionmentioning
confidence: 64%
“… 26 The chronic hyperglycemia observed in diabetes is responsible for increased advanced glycosylation end products (AGEs); accumulation of AGEs within joints can cause the load-bearing collagen proteins found in tendons and ligaments to crosslink, manifesting in biomechanical disturbance. 29 Furthermore, the association of AGEs with their endothelial receptor produces oxidative stress and the release of inflammatory cytokines, increasing vessel stiffness and permeability. 6 This aggravates the vascular environment seen in diabetes, leading to the disproportionate expression of type III collagen in tenocytes, causing greater weakness to force and susceptibility to rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The supraspinatus tendon of SD mice fed a high-fat diet showed sparse arrangement and microtears of collagen fibers at 2 weeks, and significant tearing and infiltration of inflammatory cells in tendon collagen fibers at 12 weeks. 112 By integrating the advantages and disadvantages of both monogenic animal models and DIO animal models, the selection of an appropriate animal model during experimental processes can further reflect the impact of MS on tendons.…”
Section: Establishment Of Animal Models Of Msmentioning
confidence: 99%